Factors with the greatest influence on drivers' judgment of roundabouts safety. An analysis based on web survey in Italy. (December 2018) - Distefano, Natalia; Leonardi, Salvatore; Pulvirenti, Giulia
Abstract: The aim of this paper is to identify the roundabout geometric characteristics affecting the safety perception while the typical maneuvers (entry, circulation, exit) are being carried out. The tool used was an on-line questionnaire, filled out by about 1.650 respondents. Four different dimensionality reduction methods (Cluster Analysis, Correspondence Analysis, Exploratory Factor Analysis and Confirmatory Factor Analysis) were used to analyze the data collected from the survey, in order to examine the key factors affecting the safety perception during the typical roundabout maneuvers. The considerations arising from the final model are the following: 1) the respondents' opinions regarding the safety perception of maneuvers are not preconceived ideas, but they originate from specific safety perceptions due to roundabout geometric configurations; 2) the users prefer definitely single lane roundabouts; this is an important confirmation of most results in the literature; 3) it was quantified the extent of the relationship between the safety perception of the typical roundabout maneuvers and the following aspects: a) maneuver type, b) geometric characteristics of the roundabouts design elements. This is the innovative aspect of the present research whose results have implications regarding theory, infrastructure and the application of new safety technologies. Highlights: The role of the human factor in determining the driving conduct is fundamental. Roundabouts offer best safety and operative performance among intersection at grade. Geometric characteristics may affect the perception of the maneuvers at roundabouts. A SEM model for the evaluation of the safety perception of roundabouts is proposed. Results have implications for design measures to make safer behavior in roundabouts.